2012
DOI: 10.1098/rsbl.2011.1205
|View full text |Cite
|
Sign up to set email alerts
|

Divergent host-plant use promotes reproductive isolation among cynipid gall wasp populations

Abstract: Ecological speciation occurs when reproductive isolation evolves as a consequence of divergent natural selection among environments. A direct prediction of this process is that ecologically divergent pairs of populations will exhibit greater reproductive isolation than ecologically similar pairs of populations. By comparing allopatric populations of the cynipid gall wasp Belonocnema treatae infesting Quercus virginiana and Quercus geminata, we tested the role that divergent host use plays in generating ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 18 publications
5
64
2
Order By: Relevance
“…For B. treatae , we compared the body size of asexual generation adults among populations distributed within and between host plant species. This analysis complements previous comparisons of the sexual generation [9]. For D. quercusvirens , we compared the body size of asexual generation adults among populations distributed within and between host plant species.…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…For B. treatae , we compared the body size of asexual generation adults among populations distributed within and between host plant species. This analysis complements previous comparisons of the sexual generation [9]. For D. quercusvirens , we compared the body size of asexual generation adults among populations distributed within and between host plant species.…”
Section: Methodsmentioning
confidence: 68%
“…The two sister species, Q. virginiana and Q geminata , overlap geographically in the southeastern United States, where Q. geminata is restricted to this region, but Q. virginiana stretches further up the Atlantic coast to Virginia and further west and south along the Gulf coast into Texas and Mexico [29]. We have previously demonstrated host specificity among populations of B. treatae on Q. virginiana and Q. geminata , as measured by host preference [9], [10].…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…There are six to eight different cynipid gall wasps that are highly specialized and form galls on this same live oak complex (Egan et al 2013). We have reared out many of the parasitoids from this large community, including clearly documenting the community from another gall former, Belonocnema treatae (Forbes et al 2016), but this is the first time we have observed a member of the genus Euderus in this system after two decades of work (Lund et al 1996, Egan and Ott 2007, Egan et al 2012, Egan et al 2013, Egan, unpubl. data).…”
Section: Resultsmentioning
confidence: 99%